Peranan Pemerintah Desa Dalam Pembangunan Desa Tuladenggi Kecamatan Telaga Biru Kabupaten Gorontalo - Oksin Mawikere; Juriko Abdussamad; Sri Yulianty Mozin (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The results of this study indicate that 1) the role of the village government as an innovator has been going well where the latest program is in accordance with the aspirations of the community. Moreover, the preparation of new program has been carried out using simple language which then increases interest and participation of the community in its development. 2) The role of the govemment as a facilitator has also been going well where they are able to create conducive conditions for the inflementation of development to bridge various community interests in optimizing village development it is done by involving other village government institutions such as Village Consultative Body (BPD), Family Welfare Program (PKK), Community Empowerment Institution (LPM) Dasawisma and Youth Organization (Karang Taruna). These institutions are then playing an important role to bridge the interests pf the community. Furthemore, the government also involves the Police Officers Community (Babinkabtimnas) to create a conducive environment. 3) The government’s role as a motivator has been going quite well where the village government has mobilized the community’s participation. If there are obstascles in the development process, the village government encourages and maintains the dynamics of village development by providing opportunities for the community to be able to participate directly in the implementation of it. In addition, the government has also held training to empower the community with the aim of increasing the economy in the family.